A cascaded multilevel inverter based on new basic units. Issue 12 (2nd December 2022) - Yousefizad, Shahab; Azimi, Erfan; Nasiri-Zarandi, Reza; Hafezi, Hossein
ABSTRACT: Due to the ever-increasing importance of multilevel inverters, researchers try to offer new structures for these types of inverters to improve their performance and reduce their costs. In this paper, a new topology has been proposed for cascaded multilevel inverters. This inverter is formed by the series connection of new basic units, which utilise fewer power switches in their structure. The reduction in the number of components used in this new inverter has resulted in lower economic costs and installation area. Also, four different methods have been proposed to determine the magnitudes of the input voltage sources, enabling the proposed inverter to operate in both symmetric and asymmetric modes. To show the advantages of the inverter, it is compared with the conventional cascaded H-bridge inverter and other similar ones. The simulation and experimental results confirm the performance accuracy of the proposed inverter and also its ability to generate different voltage levels at the output.